Shear stress sensitizes TRPV4 in endothelium-dependent vasodilatation. (July 2018) - Darby, William G.; Potocnik, Simon; Ramachandran, Rithwik; Hollenberg, Morley D.; Woodman, Owen L.; McIntyre, Peter
Graphical abstract: Abstract: The aim of this study was to better understand the role of TRPV4 in the regulation of blood vessel dilatation by blood flow and activation of GPCRs. Using pressure myography, the dilator responses to the TRPV4 agonist GSK1016790A and to acetylcholine, were examined in rat cremaster arterioles exposed to either no shear stress or to 200 μl/min flow for 6 min. In control vessels GSK1016709A caused vasodilatation (pEC50 7.73 ± 0.12 M, ΔDmax 97 ± 3%) which was significantly attenuated by the TRPV4 antagonists GSK2193874 (100 nM) (pEC50 6.19 ± 0.11 M, p < 0.05) and HC067047 (300 nM) (pEC50 6.44 ± 0.12 M) and abolished by removal of the endothelium. Shear conditioned arterioles were significantly more sensitive to GSK1016790A (pEC50 8.34 ± 0.11, p < 0.05). Acetylcholine-induced vasodilatation (pEC50 7.02 ± 0.07 M, ΔDmax 93 ± 2%) was not affected by shear forces (pEC50 7.08 ± 0.07 M, ΔDmax 95 ± 1%). The dilator response to acetylcholine was unaffected by the TRPV4 antagonist GSK2193874 in control arterioles (pEC50 7.24 ± 0.07 M, ΔDmax 97 ± 2%). However, in shear treated arterioles, the acetylcholine-response was significantly attenuated by GSK2193874 (pEC50 6.25 ± 0.12 M, p < 0.05) indicating an induced interaction between TRPV4 and muscarinic receptors. TRPV4 antibodies localized TRPV4 to the endothelium and shear stress had no effect on its localisation. Finally, agonist activation of the M3 muscarinic receptor opened TRPV4 in HEK293 cells. We concluded that shear stress increases endothelial TRPV4 agonist sensitivity and links TRPV4 activation to muscarinic receptor mediated endothelium-dependent vasodilatation, providing strong evidence that blood flow modulates downstream signalling from at least one but not all GPCRs expressed in the endothelium.